The skull and the portrait of Jan Kochanowski: an attempt at reconstituting the poet’s face - Dzierżykray-Rogalski, Tadeusz; Wierciński, Andrzej (Anthropological Review, 1980)
The authors relate to the case of authenticity of the certain skull thought of as belonging to the great Polish Renaissance poet Jan Kochanowski of Czarnolas. The cranium in question has been studied in 1927 and 1933 by Julian Talko-Hryncewicz and Adam Wrzosek. On grounds of anthropometric measurements taken by these two authors and an analysis of portraits of the poet the present authors put in serious doubt authenticity of thc investigated skull.